Ectopic arachnoid granulations: A review - Alvin Chitterman; Tyler Warner; Karishma Mehta; Joe Iwanaga; Marios Loukas; R. Shane Tubbs (Elsevier, 2019)
Purpose: The purpose of this review is to provide an overview of reported ectopic locations of arachnoid granulations and their potential clinical sequelae of the space-occupying lesions. Review: Arachnoid villi greater than 2 mm are termed arachnoid granulations. The hypertrophied arachnoid villi 3 cm from midline are termed "ectopic" Arachnoid granulations are usually asymptomatic, but due to their location and size, they can clinically present as non-specific symptoms of venous hypertension, including headache, nausea, vomiting, and papilledema. More specific findings have also been noted, including osteolytic lesions and otorrhea. Conclusions: Arachnoid granulations found outside their normal anatomical location are considered ectopic. Patients are usually asymptomatic but can experience a wide variety of non-specific symptoms. Keywords: Ectopic, Arachnoid granulations, Cerebrospinal fluid, Arachnoid villi